Patients with Mild Ischemic Stroke Benefit from IV-rtPA - Vinall, Phil (MD Conference Express, 2014)
There has been considerable debate regarding the use of intravenous recombinant tissue plasminogen activator (IV-rtPA) in patients with mild stroke symptoms. It has been unclear whether the potential benefits of improvement in neurologic outcomes outweigh the potential risks of hemorrhagic stroke, increased impairment, and death. This article presents results from a post hoc analysis of data from a subset of patients from the Third International Stroke Trial [IST-3; ISRCTN25765518], indicating that patients with mild stroke symptoms (ie, those having a National Institutes of Health Stroke Score of 0 to 5) may benefit from IV-rtPA.